Aerosol delivery practice in Italian Cystic Fibrosis centres: a national survey. Issue 1 (December 2016) - Gambazza, Simone; Carta, Federica; Brivio, Anna; Colombo, Carla
Abstract Background Physiotherapists (PTs) are ideally positioned to assist patients and families with inhalation therapies through monitoring, communication and education about available therapies and their proper use; indeed aerosoltherapy management is listed as part of Italian PTs' core competence and in the core syllabus for post-graduate training in respiratory physiotherapy. The aim of this study was to outline the involvement of Italian PTs working in Cystic Fibrosis (CF) centres in the aerosol delivery practice. Methods Physiotherapist coordinators (n = 29) of all Italian CF centres were invited to participate in a cross-sectional survey and a semi-structured questionnaire was developed and sent by e-mail. Results A response rate of 69 % was achieved. The majority of participants were woman and the overall mean professional experience was twenty years. Italian PTs are involved in the aerosol delivery practice, managing education, drug-device combination, dilution and mixing of drugs. Conclusions Physiotherapists play a key role in the care of Italian CF patients; nevertheless the Italian Group of Physiotherapists might plan interventions to harmonize the aerosol delivery practice in Italian CF centres and to sustain continuing education.